The clinical utility of human leucocyte antigen B27 in axial spondyloarthritis. (25th September 2017) - Lim, Chong Seng Edwin; Sengupta, Raj; Gaffney, Karl
Abstract: The association between HLA-B27 and AS was first established in the early 1970s. Since then, our understanding of this disease has changed, such that we now recognize AS to be the extreme of the clinical phenotype within a disease spectrum known as axial SpA (axSpA). Recent advances in therapeutic options have driven the need for earlier diagnosis and many screening strategies have been proposed to facilitate this. In parallel, our understanding of axSpA genetics, and especially the contribution of HLA-B27, has expanded. In this article we will present and discuss the evidence supporting the use of HLA-B27 in clinical practice. We will briefly summarize the evolution of the concept of axSpA, the prevalence of HLA-B27 and axSpA and the potential role of HLA-B27 in the aetiopathogenesis of axSpA and focus on the utility of HLA-B27 in everyday clinical practice.